(untitled) (Biological Sciences - PJSIR, 1995)
Ecdysteroids have been isolated and quantified from the roots of Aerva tomentosa (0.035%) and the aerial parts of Pandiaka involucrata (0.3%). The latter has been found as one of the best source of20-hydroxyecdysone in plants, traces of 5,20-dihydroxyecdysone have also been detected from it.